Immunohistoochemical evaluation of GATA-3, pAKT and Ki-67 in triple negative breast carcinoma - Aryal, Gopi; Chhetri Aryal, Sameer; Soejima, Yurie; Sheckler, Victoria; Eishi, Yoshinobu; Sawabe, Motoji (Journal of Pathology of Nepal, 2017)
Background: Triple-negative breast cancers lack expression of estrogen receptor, progesterone receptor, and human epidermal growth factor receptor -2. These tumors have been known to be clinically aggressive. We evaluate GATA-3, pAKT and Ki-67 expression in 35 triple negative breast carcinomas. Materials and Methods: A total of 35 triple negative breast carcinomas were included in this study. The histological subtyping was done according to Japanese guidelines for breast cancer. Results: GATA-3 was positive in 60% (21/35) of tumors. High GATA-3 expression was observed in ductal carcinoma in situ. pAKT expression was demonstrated in 85.7 % (30/35) of TNBCs. The levels of expression of GATA-3 and pAKT showed no significant association with nuclear grading. (P=0.761 and P=0.487, respectively). Ki-67 labeling index was positively correlated with nuclear grading (p<0.001). Conclusion: GATA-3 expression has no relation with ER and PR expression and pAKT and GATA-3 are strongly expressed in TNBCs.